KOLOM PIPA BAJA MEMIKUL STRUKTUR RANGKA CANTILEVER - Immanuel Panusunan Tua Panggabean (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
It is commonplace when architectural designs that require beauty often do not pay attention to the strength of building structures as part of a unity of structures and architecture of buildings, forgetfulness of the part of the building that was originally assumed not to bear the burden in the end should bear the burden causing a new design adjustment. The study of pipe columns as poles on cantilever building structures was studied because of the concerns of the building owner and also the construction executor of the cantilever frame design. The position of the pole as a successor to the load from the roof to the foundation is noticed because the steel material is elastic and also weak against buckling. An examination of the modified section of the frame structure is absolutely necessary to increase the stiffness of the structure, so that the pipe columns with small dimensions according to the architectural design can be maintained.